The Policy Analysis Matrix in Measuring Competitiveness of Maize Farming System in Marginal Areas - Lorenta In Haryanto; Masyhuri Masyhuri; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
Yellow maize for animal feed is one of potential strategic commodities to be developed in Pacitan Regency, as a marginal area. The focusing question is whether this commodity generates competitiveness. This research aims: 1) to determine the private and social profitability, 2) to analyze competitiveness through comparative and competitive advantages, 3) to discuss effects of government policies on maize farming system. Data were analyzed by using the Policy Analysis Matrix (PAM) method. A sampling area was purposively selected, i.e. Pacitan Regency, while 102 maize farmers were proportionally selected as respondents. The research covers three seasons: rainy season I, rainy season II, and dry season. The result of analysis shows that in the rainy season II, maize farming in Pacitan generates private and social profits and competitiveness as indicated by the Private Cost Ratio (PCR) and the Domestic Resource Cost Ratio (DRCR) of less than one. The maize farming in the rainy season I and the dry season does not generate either profit or competitiveness. In general, the level of government protection of agricultural outputs is considered low but the protection of both tradable and non-tradable agricultural inputs is high. The government policy on agricultural outputs and inputs simultaneously does not protect maize farming effectively.